LA VULNERACIÓN DE LA CADENA DE CUSTODIA CONLLEVA A LA IMPUNIDAD EN EL ÁMBITO PENAL - Rogel Celi., Jhon Iván (2021)
This research work is based on "THE INFRINGEMENT OF THE CHAIN OF CUSTODY LEADS TO THE CRIMINAL FIELD IMPUNITY" Chain of Custody applied to the results of the infringement, the Ecuadorian criminal justice system takes important because once collected the evidence in the scene, help prove to discard the commission of a crime. Hence the Criminal Procedure also has among its purposes the grasp or keep safe all these elements of substance, essential in the process. Chain of Custody, can know where the evidence, who are the people responsible, the name of the expert or experts involved, research, etc. For this part can say that the chain of custody is a set of procedures are security, mainly to ensure that material evidence or physical evidence identified, fixed, harvested, packed and labeled, is the same that was in place explored and found equal phenomenological conditions that had the item there. Therefore, protecting the integrity of evidence and evidence, is an important tool for law enforcement factor; but if the integrity of the sign or evidence is questioned, it may jeopardize their employment during the trial stage and perhaps the possibility of submitting a guilty person to justice. In order to properly identify evidence should be classified on the basis of predetermined technical parameters stipulated in the legal system, 5 particularly in the criminal field where more importance should be observed the principle of legality. Hence it is very important that anyone who drives a sign or evidence during an investigative process, be familiar with the rules and procedures governing the chain of custody and comply fully, bearing in mind that the chain of custody begins where-is obtained or collected all evidence, whether a material or physical element and ends by order of the competent authority. Finally, the collection of theoretical and legal and doctrinal information, conducting surveys and interviews helped me to be able to issue grounded, clear and specific criteria, with an extensive and varied literature, which allowed us to verify the objectives and in turn the test of the hypothesis.